Picosecond-scale ultrafast many-body dynamics in an ultracold Rydberg-excited atomic mott insulator - Bharti, Vineet; Sugawa, S.; Mizoguchi, M.; Kunimi, M.; Zhang, Y.; de Léséleuc, S.; Tomita, T.; Franz, Titus; Weidemüller, Matthias; Ohmori, K. (Physical review letters, 2023)
We report the observation and control of ultrafast many-body dynamics of electrons in ultracold Rydberg-excited atoms, spatially ordered in a three-dimensional Mott insulator (MI) with unity filling in an optical lattice. By mapping out the time-domain Ramsey interferometry in the picosecond timescale, we can deduce entanglement growth indicating the emergence of many-body correlations via dipolar forces. We analyze our observations with different theoretical approaches and find that the semiclassical model breaks down, thus indicating that quantum fluctuations play a decisive role in the observed dynamics. Combining picosecond Rydberg excitation with MI lattice thus provides a platform for simulating nonequilibrium dynamics of strongly correlated systems in synthetic ultracold atomic crystals, such as in a metal-like quantum gas regime.